2016
DOI: 10.1007/s10886-016-0759-y
|View full text |Cite
|
Sign up to set email alerts
|

Response to Heethoff, Norton, and Raspotnig: Ant and Mite Diversity Drives Toxin Variation in the Little Devil Poison Frog and Erratum

Abstract: Our recent publication titled "Ant and Mite Diversity Drives Toxin Variation in the Little Devil Poison Frog" aimed to describe how variation in diet contributes to population differences in toxin profiles of poison frogs. Some poison frogs (Family Dendrobatidae) sequester alkaloid toxins from their arthropod diet, which is composed mainly of ants and mites. Our publication demonstrated that arthropods from the stomach contents of three different frog populations were diverse in both chemistry and species comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Characterization of the chemical defenses of mites is also hindered by the status of mite taxonomy and dearth of mite taxonomists, an uncontroversial point made by McGugan et al (2016b). The number of oribatid mites is on a par with ants (roughly 14,000 species); Schatz et al (2011) reported 16,197 extant species of oribatid mites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Characterization of the chemical defenses of mites is also hindered by the status of mite taxonomy and dearth of mite taxonomists, an uncontroversial point made by McGugan et al (2016b). The number of oribatid mites is on a par with ants (roughly 14,000 species); Schatz et al (2011) reported 16,197 extant species of oribatid mites.…”
Section: Discussionmentioning
confidence: 99%
“…They attempted to identify the arthropod species (ants and mites) responsible for the alkaloid diversity in the little devil poison frog, Oophaga sylvatica, by coupling molecular phylogenetic identi cation of prey with characterization of alkaloids both in the prey and in the skin of the predator frog. McGugan et al (2016b) retrieved 137 ants and 102 mites from the stomachs of frogs of three populations of O. sylvatica. Here we focus only on the mites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation